Magnesium-L-theanine complex protects against liver and intestinal damage caused by chronic variable stress - Şahin, Kazım; Yabas, Mehmet; Orhan, Cemal; Er, Besir; Ozmen, Ramazan; Tokmak, Muhammed; Şahin, Nurhan (Cambridge Univ Press, 2026)
Chronic stress can lead to serious health problems, including elevated blood glucose, intestinal dysbiosis, villous shortening, decreased enzyme activity and hepatic steatosis. Here, we investigate the protective effects of the magnesium-L-theanine (Mg-T) combination on chronic variable stress (CVS)-induced liver and intestinal damage. Fifty-six rats were divided into two groups: normal and stressed, and supplemented with different doses of Mg-T (0, 100, 200 and 400 mg/kg). The results showed that CVS-treated rats had reduced body weight, serum insulin levels, magnesium levels, intestinal barrier proteins and nutrient transporters. However, Mg-T supplementation improved these parameters in a dose-dependent manner. Mg-T treatment reduced CVS-induced glucose, corticosterone and triglyceride levels while alleviating liver and intestinal damage. Histological analysis revealed that Mg-T alleviated CVS-induced intestinal damage, characterised by villus shortening, reduced crypt depth and inflammation. CVS-induced increases in hepatic triglycerides and lipogenic markers (SREBF1, FASN) were attenuated by Mg-T supplementation, while metabolic regulators such as PPAR gamma and SIRT-1 were upregulated. Moreover, Mg-T restored the expression of intestinal barrier proteins (Claudin-1, Occludin, ZO-1) and mucosal protein (MUC-2). CVS treatment reduced the expression of nutrient transporters (SGLT1, GLUT2) and amino acid carriers; however, Mg-T supplementation increased the protein levels of these markers. Our data demonstrate that Mg-T has significant protective effects against CVS-induced metabolic, hepatic and intestinal disturbances, highlighting its potential as a therapeutic intervention for managing chronic stress-related health problems.
Keywords: Chronic variable stress; Inflammation; Intestine; Magnesium-L-theanine